Heavy slow resistance training, radial extracorporeal shock wave therapy or advice for patients with tennis elbow in the Norwegian secondary care: a randomised controlled feasibility trial - Jens Ivar Brox; Marianne Bakke Johnsen; Cecilie Roe; Aasne Fenne Hoksrud; Håkon Sveinall; Kaia B Engebretsen (BMJ Open)
Objectives To evaluate the feasibility of recruitment, appointment adherence, intervention compliance, acceptance and comprehensibility, in addition to retention rate and data completeness. An ancillary aim was to describe within-group changes in the secondary outcome measures (patient-reported and performance-based).Design A single-centre, three-armed, randomised controlled feasibility trial with a parallel design, with follow-up after 3 and 6 months.Setting Participants were recruited from the outpatient clinic at Oslo University Hospital.Participants Patients with lateral epicondylalgia, commonly known as tennis elbow.Interventions Participants were randomised in a 1:1:1 ratio to heavy slow resistance training, radial extracorporeal shock wave therapy or information and advice.Main outcome measures Feasibility was assessed according to a priori criteria for success.Results In total, 89 patients were screened for eligibility, and 69 (78%) patients were eligible for randomisation. 60 (92%) participants were randomised which gave a recruitment rate of 3.4 per month (against an a priori success cut-off of 3.75). The participants rated all the interventions as acceptable and comprehensive. Only 6 of 19 (32%) did comply with heavy slow resistance training. Retention rate and completeness of data were successful at 3 months. At 6 months, the retention rate was below the criteria for success. Patient-reported and performance-based outcomes improved in all groups.Conclusion The current study shows that the process of recruitment and the retention rate at follow-up can be feasible with minor amendments. Participants had low compliance with heavy slow resistance training mainly due to pain aggravation, which suggests that this intervention was not suitable for patients with tennis elbow. Shock wave therapy and information and advice should be investigated further in a full-scale randomised controlled trial including sham shock wave therapy.Trial registration number NCT04803825.